The narrative personage and the passions. The construction of the subjectivity - de Lima, Eliane Soares (Laboratório Editorial FCL-UNESP, 2008)
Understanding the personage as a diffuse signification unit, progressively constructed by the narrative, and being, therefore, its resulting and inherent part, this article proposes a reflection about the process of subjectivity of the verbal beings, what results in a complex and autonomous structure and confuses the reader considering the walls that split reality and fiction. Then, making use of the Passion Semiotics theory and its methods of analysis, we try to sketch a reasoning line capable of a contribution for a study of the personage, in its specificities as a being-language.